The Problem of Aim of Science in the Philosophy of Scientific Realism - Maidanskaya, Irina A.; Kuznetsov, Andrey V.; Reznik, Sergey V.; Rimsky, Viktor P.; Mariasova, Elena A. (Journal of History Culture and Art Research, 2017)
The article deals with the problem of immanent aim of the scientific cognition. The relationship between science and reality is viewed from the standpoint of scientific realism, resting upon the axiom that theories are assertions about the reality independent of human experience and even of reason itself. The authors argue that the adoption of scientifically-realistic ideal of science gives us a simple and reliable criterion the demarcation of scientific and non-scientific knowledge. But the scientific realism can go beyond the bounds of “philosophical belief” only having turned itself towards the world of objectively practical activity – into the world of “artifacts”, created by human labour. It is in this objective world of material culture scientific theories are being “verified” or “falsified”, and science, in a whole, finds its highest aim and implementation. The authors conclude that the study of the “fourth world” of material culture, in which science finds its true practical implementation, should be the cornerstone of scientific realism.